Perancangan Alat Lift Table Mengunakan Actuator Linear Untuk Optimalisasi Operasional Tenaga Kerja - Prayoga , Made; Madagaskar; Kohar (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
The development of technology in the industrial sector is currently growing rapidly, especially those related to automation and production efficiency. The technology widely used in industry is a lifting table tool, which is used to raise and lower loads vertically. This lifting table uses a linear actuator as its driving force. The purpose of this lift table design is to develop a reliable, efficient, and safe system.                 Literature Study, the author looks for data by reading catalogs or literature books that are related to the title of the thesis that the author took. Field study Is a method of collecting data that comes directly to the object to be reviewed by collecting all the data in the field Using electric current At a load of 25 kg, the lifting time is 7.20 seconds. At a load of 50 kg, the lifting time is 10.21 seconds. At the last load, namely a load of 75 kg, it takes 14.23 seconds to lift the load. And for the second method, namely Using power from the battery At a load of 25 kg for lifting the load takes 36.13 seconds, at a load of 50 kg takes about 42.26 seconds and for the last load of 75 kg takes 58.45 seconds to lift the load. From the test results obtained the maximum load that occurs on the frame is 139.561 N